2009
DOI: 10.1590/s1678-91992009000300020
|View full text |Cite
|
Sign up to set email alerts
|

Role of TLR2 and TLR4 on human neutrophil functions against Paracoccidioides brasiliensis

Abstract: In paracoccidioidomycosis, a systemic mycosis caused by the fungusParacoccidioides brasiliensis (Pb), studies have focused on the role of neutrophils that are involved in the primary response to the fungus. Neutrophil functions are regulated by pro-and anti-inflammatory cytokines. Molecular mechanisms involved in this process are not fully understood, but there are strong evidences about the involvement of toll-like receptors (TLRs). We aimed at evaluating TLR2 and TLR4 expression on human neutrophils activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 0 publications
2
16
0
4
Order By: Relevance
“…In the present study, a macroscopic examination of scalp, skin and nails for the 36 culture positive patients revealed 2.2% Tinea capitis, 13 In ESRD, uremia is associated with immune-suppression due to the impact of uremic milieu and a variety of associated disorders exerted on immunocompetent cells. Hypercytokinemia is a typical feature of uremia, likely due to accumulation of pro-inflammatory cytokines as a consequence of decreased renal elimination and/or increased generation following induction by uremic toxins, oxidative stress, volume overload, comorbidities etc.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In the present study, a macroscopic examination of scalp, skin and nails for the 36 culture positive patients revealed 2.2% Tinea capitis, 13 In ESRD, uremia is associated with immune-suppression due to the impact of uremic milieu and a variety of associated disorders exerted on immunocompetent cells. Hypercytokinemia is a typical feature of uremia, likely due to accumulation of pro-inflammatory cytokines as a consequence of decreased renal elimination and/or increased generation following induction by uremic toxins, oxidative stress, volume overload, comorbidities etc.…”
Section: Discussionsupporting
confidence: 49%
“…11 Virulence factors of dermatophytes contribute to the modulation of the host immune response and can be expressed throughout the whole infectious process. [12][13] Several studies suggested that the immunosuppressive properties of the mannans was responsible for the chronicity of dermatophytosis especially caused by Trichophyton rubrum and was less inflammatory in individuals with impaired functions of T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…An adaptive immune response is modulated and shaped by efficient innate recognition of pathogens through pattern recognition receptors (PRRs) (4). Specifically, P. brasiliensis is sensed by TLR-2 and TLR-4 (5,6), and the engagement of these receptors by pathogens triggers the activation of macrophages, which produce inflammatory cytokines by a MyD88-dependent pathway. Importantly, MyD88 2/2 mice infected by P. brasiliensis demonstrate high susceptibility but produce significant amounts of cytokines.…”
mentioning
confidence: 99%
“…The expression of TLR-2 molecule on polymorphonuclear granulocytes has been studied with respect to infection, sepsis, surgical stress and other medical interventions. This early TLR-2 down-regulation may be the result of externalizing entire molecules rather than transcriptional regulation of TLR-2 biosynthesis 39,40 . The intensity of TLR-2 expression on granulocytes is also significantly reduced during cardiopulmonary bypass surgery 41 .…”
Section: Discussionmentioning
confidence: 99%